Montelucaste diminui as crises convulsivas em animais abrasados e potencializa o efeito anticonvulsivante do fenobarbital - Fleck, Juliana (2015)
Epilepsy is a chronic neurological disease characterized by recurrent, unprovoked seizures. Evidence suggests that inflammation plays a role in the pathophysiology of seizures. Although cysteinyl leukotrienes (CysLTs) have been implicated in seizures, no study has investigated whether blocking of CysLT1 receptors potentiates the anticonvulsant action of classic antiepileptic drugs, as well as the expression of CysLT receptors is altered by inflammation. In this study we showed that the inverse agonist of CysLT1 receptor, montelukast, synergistically increases the anticonvulsant action of phenobarbital against seizures induced in a model of acute injection of pentylenetetrazole (PTZ). Furthermore, it is shown that LTD4 (leukotriene D4) prevents the effect of montelukast. Isobolographic analysis revealed an ED50 mix value for a fixed-ratio combination (1:1 proportion) of montelukast plus phenobarbital of 0.06 ± 0.02 μmol, whereas the calculated ED50 add value was 0.49 ± 0.03 μmol. The interaction index was 0.12, indicating a synergistic interaction. Montelukast significantly decreased the antiseizure DE50 for phenobarbital (0.74 and 0.04 μmol in the absence and presence of montelukast, respectively) and, consequently, phenobarbital-induced sedation at equieffective doses. We also investigated whether the CysLT1 inverse agonist montelukast and a classical anticonvulsant, phenobarbital, decrease seizures in PTZ-kindled mice and CysLT receptor expression. Montelukast (10 mg/kg, s.c.) and phenobarbital (20 mg/kg, s.c.) increased the latency to generalized seizures in kindled mice. Montelukast increased CysLT1 immunoreactivity only in non-kindled PTZ-challenged mice. Interestingly, PTZ challenge decreased CysLT2 immunoreactivity only in kindled mice. CysLT1 antagonists seem to emerge as promising adjunct therapeutic agents in the treatment of refractory seizures. Notwithstanding, additional studies are necessary to evaluate the clinical implications of this work.